LEARNING ANALYTIC TO FACILITATE GROUP NETWORK COLLABORATION - Evgeny D. Patarakin (Высшее образование в России, 2016)
This paper presents the general principles of learning design of collaborative network, according to which the activity of learning agents is built around the creation of various types of educational digital objects. These objects in general can be described as«digital story». Due to the fact that the network activity is associated with creation and changes in digital objects, organizers and participants of the activity have an opportunity toobserve, analyze and discuss the situation of the collaboration. Here presented the methodology of using diagrams of collaboration on the board with alphanumeric notation, which allows discussing and analyzing of qualitative data about the group members, which are formed in the course of training or social and educational projects. The analysis of real cases shows that the technology and methodology of static and dynamic diagrams help to analyzeand discuss situations that happen during collaborative activities.